PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT GIKEN PRECISION INDONESIA - Lery Setyawati, Putu Wida Augustina; Hikmah, Hikmah (LPPM Universitas Putera Batam, 2022)
This research aims to find out how the influence of compensation and work motivation onemployee performance that occurs at PT Giken Precision Indonesia. PT Giken PrecisionIndonesia itself is a company engaged in manufacturing electronics.At PT Giken PrecisionIndonesia there are approximately 1967 employees who are divided into four departments,namely Hq, Assembly, PCB, and Molding, but the population in this study are employeesof one of the departments of PT Giken Precision Indonesia, namely the Assemblydepartment with a sample of 184 respondents. . This study uses quantitative methods withdescriptive research types and to analyze data using descriptive methods, determinationand multiple linear regression which were tested using a tool, namely SPSS (StatisticalProduct and Service Solution) version 25, data were collected through questionnaireswhich were then analyzed. Then the results obtained from the data analysis test show thatcompensation and work motivation have a significant positive effect on employeeperformance at PT Giken Precision Indonesia although there are other influences outsideof the research discussion, namely compensation and work motivation that can affectemployee performance